Zoogeographic analysis of Chilopoda and Diplop-oda of the fauna of the Central Ciscaucasia - Sergey Ivanovich Sigida; Roman Vladimirovich Zuev (Наука. Инновации. Технологии, 2022)
There is a zoogeographical analysis of 55 species of centipedes and millipedes of the Central Ciscaucasia. It was revealed that in the formation of the fauna of this region, the most important were species that refer to the Boreal, Mediterranean and Caucasian zoogeographic complexes. This is due to the location of the region on the border of the three subregions of the Palaearctic: the European-Siberian, Mediterranean and Central Asian. The largest number of species belongs to the endemics and subendemics of the Caucasus, which is especially pronounced in Diplopoda. The second most numerous species is the Boreal complex. The Mediterranean complex is heterogeneously represented in centipedes and millipedes: in Chilopod it contributes approximately equal to the Boreal and Caucasian complexes, while for diplopods its value is on the contrary small. The range of areas that extend beyond the Holarctic is represented by anthropochronic species.